Pemberdayaan Masyarakat Melalui Pokdarwis dalam Pengembangan: Kasus Ekowisata Air Terjun Curup Kereta - Lestari, Amilia; Muljono, Pudji; P. Lubis, Djuara; Virianita, Ratri (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2025)
This study aims to analyze the role of the Tourism Awareness Group (Pokdarwis) in empowering the community through the development of ecotourism at Curup Kereta Waterfall. A qualitative approach was used, employing data collection techniques such as in-depth interviews, observations, and documentation. Pokdarwis plays a vital role in enhancing community capacity through tourism management, environmental conservation, and visitor services. The findings reveal that community involvement in Pokdarwis contributes to local economic growth by providing tourism services and local products. However, this empowerment faces challenges such as suboptimal coordination with the Tourism Office and limited infrastructure to support accessibility and visitor comfort. Furthermore, community participation in decision-making remains confined to implementation aspects. To ensure the sustainability of ecotourism, greater equitable community involvement and improved coordination between Pokdarwis, the government, and other stakeholders are required. These findings highlight the critical role of Pokdarwis as an empowerment agent, bridging the community with sustainable ecotourism opportunities and fostering inclusive and continuous prosperity.